The Influence Of Hoop Media On Chest Pass Accuracy In Basketball - Finny Rohaeni; Agus Gunawan; Nunuh Saepudin; Dewi Susilawati (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research aims to determine the effect of hoop media on chest pass accuracy in basketball. Where students still make a lot of mistakes when passing, especially when doing the chest pass technique, so that the accuracy in passing the ball is not on target to teammates. Given these problems, this research attempts to create a training program to make it easier for students to do chest passes in the game of basketball using hoops. The method used is Quasi-Experimental. The population of this study were students who took part in basketball extracurricular activities at SDN Jatiendah Kab. Bandung. Data was collected through the pretest and posttest stages using the AHHPERD test research instrument. The final result of this research was Sig. 0.000 because a = <0.05, which means there is an influence of hoop media on the accuracy of chest pass targets in basketball. The magnitude of the influence of the hoop media on the accuracy of the chest pass target was obtained by correlation results, namely 0.598, which if entered in percent form becomes 59.8%. With these findings, it can be concluded that the application of training using hoops has a positive influence, and makes a strong contribution to students' ability to do chest passes on target using hoops.